World War I: A Phoenix Moment in the History of International Criminal Tribunals. (26th September 2022) - Bohrer, Ziv; Pirker, Benedikt
Abstract: The post-World War II International Military Tribunal at Nuremberg is commonly considered the first-ever international criminal tribunal. It is also often argued that the very idea of an international criminal tribunal emerged after World War I, when the first plans for such a tribunal were drawn up. This article, however, presents a very different account. It shows that international criminal tribunals did not have to wait for their conception until after World War I; nor did they come into being after World War II – they already operated during World War I and the preceding century. The article also demonstrates that the existence of such tribunals did influence the participants of the Paris Peace Conference, even though they portrayed them as novel.